2012
DOI: 10.4997/jrcpe.2012.302
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuron-specific enolase and S100 calcium binding protein B biomarker levels do not improve diagnosis of acute stroke

Abstract: Background:The high sensitivities and specificities reported for blood biomarkers as a supportive test in the diagnosis of acute stroke do not correspond with their performance for decision-making in emergency situations. Methods: Seventy-two patients with suspected stroke were recruited: 44 with ischaemic stroke, 17 with haemorrhagic stroke and 11 stroke mimics, as well as a high-risk control group of 79 individuals. Serum neuron-specific enolase (NSE) and S100 calcium binding protein B (S100B) biomarker leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, no control group of patients without CNS disorders was examined. Another recent study found only a low sensitivity of 55% for detecting stroke in a mixed IS and ICH population when analyzing S100β in a 12- to 48-h time window since symptom onset [32]. It is unclear whether these discrepancies are caused by different preanalytical procedures or by the assays used to detect S100β.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no control group of patients without CNS disorders was examined. Another recent study found only a low sensitivity of 55% for detecting stroke in a mixed IS and ICH population when analyzing S100β in a 12- to 48-h time window since symptom onset [32]. It is unclear whether these discrepancies are caused by different preanalytical procedures or by the assays used to detect S100β.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 61 acute stroke patients, González‐García S. et al showed that blood S100β was elevated in stroke patients between 12 and 48 h after symptoms onset compared with high‐risk controls. Although its levels did not correlate with severity, it could discriminate ( p < .001) between lacunar and non‐lacunar IS 68 . Additionally, Foerch et al 69 measured the protein kinetics and showed that peak values can occur until 96 h after symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…[12,23]. Although S100B been linked to cerebral ischaemia, developing it into a biomarker for differential diagnosis in clinical practice has been problematic [24,25]. Several writers have claimed that elevated levels of S100B in the blood are not unique to stroke, claiming that the rise occurs in other neurological disorders with similar symptoms [26].…”
Section: Discussionmentioning
confidence: 99%